The Effect of Technological Organization on Cost Innovation and Value Creation - Jintanee Ru-Zhue; Somnuk Aujirapongpan; Yaninee Songkajorn; Kritsakorn Jiraphanumes (Emerging Science Journal, 2022)
This research aims to study the effects of technological organization, management of cost innovation, and value creation. The population in this study was the canned and instant food export companies, which are crucial industries that earn incomes for Thailand. The quantitative research method was carried out using questionnaires sent to all companies (census) with the manufacturing managers as respondents. The survey revealed that these companies had a high level of technological organization, value creation, and cost innovation, except for reducing unnecessary functions at a moderate level because the products need to maintain customer demand; therefore, unnecessary adjustments may not be made. PLS-SEM assesses the reflective and structural models to test the research hypotheses. The findings revealed significant influences among three pairs of constructs: (1) technological organization had a positive effect on cost innovation, (2) cost innovation had a positive effect on value creation, and (3) technological organization had a positive effect on value creation. Thus, this research provides empirical information for the influences among the variables and presents the significance of being a technological organization and the inclusion of cost innovation management, to maintain their business during the COVID-19 pandemic and improve the organizational potential for preparation in future circumstances. Doi: 10.28991/ESJ-2022-06-02-09 Full Text: PDF